2020
DOI: 10.3233/blc-200275
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Short-Term Oncological Outcomes of Thulium Fiber Laser En Bloc Resection of Non-Muscle-Invasive Bladder Cancer: A Prospective Non-Randomized Phase II Trial

Abstract: BACKGROUND: Ongoing efforts aim at overcoming the challenges of conventional transurethral resection of bladder tumor (TURBT) such as the high recurrence rate, difficulty of pathologic interpretation and complications including wall injury. OBJECTIVE: To prospectively assess the safety and efficacy of Thulium fiber en bloc resection of bladder tumor (Tm-fiber ERBT) compared to TURBT. MATERIALS AND METHODS: The prospective non-randomized study included 129 patients with non-muscle-invasive bladder cancer (NMIBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…Also, TFL ERBT demonstrated a lower complication rate (like obturator nerve reflex, perforation) and better specimen quality compared to conventional TURBT (showing better detrusor rate on pathology). The only reported disadvantage for TFL ERBT was the prolonged surgery duration time (39.0 ( ± 16.5) vs 34.0 ( ± 8.8) min for TURBT) (41).…”
Section: Thulium Fiber Laser For Soft Tissues: Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, TFL ERBT demonstrated a lower complication rate (like obturator nerve reflex, perforation) and better specimen quality compared to conventional TURBT (showing better detrusor rate on pathology). The only reported disadvantage for TFL ERBT was the prolonged surgery duration time (39.0 ( ± 16.5) vs 34.0 ( ± 8.8) min for TURBT) (41).…”
Section: Thulium Fiber Laser For Soft Tissues: Clinical Trialsmentioning
confidence: 99%
“…BPH surgery aside, TFL proved itself to be a suitable device for en bloc resection of bladder tumor (ERBT), predominantly NMIBC, within a prospective clinical trial (41). It was shown that patients after TFL ERBT had a better relapse-free rate than TURBT at both 3 (97.2% and 84.5%, p = 0.011) and 6 months (91.5% and 67.2%, p < 0.001).…”
Section: Thulium Fiber Laser For Soft Tissues: Clinical Trialsmentioning
confidence: 99%
“…At the time of writing, there is a published paper by Enikeev and colleagues who look at the safety and short-term oncological outcomes of TFL for EBRT. 40…”
Section: Bladder Tumoursmentioning
confidence: 99%
“…Previous studies using Thulium laser found that obturator jerk occurs more with conventional TURBT than with Thulium laser en bloc resection. [ 5 - 7 ] This is due to the absence of electric current in LASER resection and the shallow penetration of LASER. Monopolar en bloc resection would not obviate obturator jerk as reported by Yang et al .…”
Section: Discussionmentioning
confidence: 99%